Evaluation of dentists? knowledge of the use of oral exfoliative cytology in clinical practice - Weber Adorno Silva; Ana Paula de Lima; Luana Marotta Reis De Vasconcellos; Ana Lia Anbinder (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Oral exfoliative cytology (EC) is a rapid and practical complementary test that can be used in the diagnosis of various diseases. The objectives of this study were to assess dentists' knowledge of EC and to disseminate information on the technique. The study included 240 dentists from the city of Anápolis (Goiás, Brazil) who answered a questionnaire regarding demographic data and data relating to EC and who then received information on the technique. The data revealed that 26.92% of the dentists did not know about EC. Among those who reported knowledge of EC, 33.91% did not know the procedures for performing the technique, and 85.38% had no experience with EC. In addition, 54.09% of the answers regarding the instrument used to collect the material and 56.82% of the answers concerning suitable fixatives were inappropriate. Although 73.02% of the dentists adequately identified the pathologies for which EC is recommended, it was concluded that the respondents had poor knowledge of EC. There is a need to increase dentists' awareness of this subject and of EC's use in diagnostic practices.